Customs Brokerage Services and Trade Facilitation: A Review of Regulatory Coherence - Gilberto M. Llanto; Adoracion M. Navarro; Keith C. Detros; Ma. Kristina P. Ortiz (Philippine Institute for Development Studies (PIDS), 2013)
The study looks at the rarely studied customs brokerage activity in the Philippines and its role in facilitating trade given the ongoing push to modernize customs administration. It analyzes how the customs brokerage profession is being regulated and synthesizes insights on opposing views on the importance of customs brokers in trade facilitation. The results of the study clearly point toward a declining relevance of the customs brokers' services in an environment where customs administration is modernizing, computerization is replacing the traditional, direct interaction of brokers with the Bureau of Customs, and a more transparent customs administration is emerging to efficiently process a significantly growing volume of trade transactions.Understandably, a threatened profession such as brokering mounts resistance in the face of changes. Customs brokers take the Customs Brokers Act of 2004 as their shield against any attempt to dilute or minimize their role in the customs administration process. However, their legalistic stand somewhat collides with the policymakers' attempt to modernize customs administration. A more positive outlook on modernization should trigger among customs brokers a paradigm shift, namely, that a modernized customs administration and trade facilitation process will necessarily create new opportunities for those adept and flexible enough to adjust to changing market conditions. Moreover, it will be more efficient and consistent with trade facilitation to allow traders to use various and modern options for releasing or shipping their goods.
Keywords: 330; trade facilitation; ASEAN Economic Community (AEC); customs brokerage